Detection and analysis of bovine foamy virus infection by an indicator cell line - Ma Zhe; Qiao Wen-tao; Xuan Cheng-hao; Xie Jin-hui; Chen Qi-min; Geng Yun-qi (Acta Pharmacologica Sinica, 2016)
Aim: To determine the infectivity and replication strategy of bovine foamy virus (BFV) in different cultured cells using the BFV indicator cell line (BICL) system. Methods: BFV infection was induced by the co-culture method or the transient transfection of the infectious BFV plasmid [pCMV (cytomegalovirus) - BFV] clone. The infectivity of BFV was monitored by the percentage of green fluorescent protein-positive cells in the BICL. The effect of reverse transcriptase inhibitor zidovudine (AZT) on BFV replication was also evaluated in the BICL. Results: The titer of BFV in fetal bovine lung cells was 4-5-folds more than that in either 293T or HeLa (Cells from Henrietta lacks) cells using the co-culture method, and in the meantime was significantly higher than that produced by the infectious clone pCMV-BFV in the same cells. AZT had only a minor effect on viral titers when added to cells prior to the virus infection. In contrast, viral titers reduced sharply to the level of the negative control when the virus was produced from cells in the presence of AZT. Conclusions: BICL can be used for the titration of the BFV viral infection in non-cytopathic condition. In addition, we provide important evidence to show that reverse transcription is essential for BFV replication at a late step of viral infection.